A Comparative Study of Liver and Kidney Function Indicators in Patients with Beta-thalassemia Major and Beta-thalassemia Trait - Enaam AL-Dagestani; Mohammad Hamza; Nabaa Yusif (Al-Anbar Medical Journal, 2025)
Background: Comparative analysis of liver and kidney function in patients with beta-thalassemia major (BTM) and beta-thalassemia trait (BTT) is relatively underexplored in the existing literature.Objectives: This study compares liver and kidney function in children with BTM, BTT, and healthy controls, and investigates the potential protective role of ferritin in reducing iron-related tissue damage in BTT patients. Materials and methods: A case-control study was conducted on 93 male children (ages 2–12) from Ibn Al-Atheer and Ibn Sina Hospitals in Mosul, Iraq, divided into three groups: BTM (31), BTT (31), and healthy controls (31). Serum levels of liver and kidney biomarkers (ALT, AST, ALP, DBIL, TBIL, urea, creatinine, uric acid, and ferritin) were measured. Statistical analysis was performed using SPSS (version 26.0) with a significance level of P-value < 0.05.Results: In the BTM group, levels of ALP, AST, urea, and uric acid were significantly higher compared to the control group, while no significant differences were observed between the BTT and control groups for these parameters. ALT, TBIL, DBIL, creatinine, and ferritin levels were elevated in both BTM and BTT groups relative to controls. Notably, all parameters except TBIL were significantly higher in the BTM group than in the BTT group. Additionally, a significant positive correlation was observed between ferritin and ALP in the BTM group, whereas a significant negative correlation was found between ferritin and creatinine in the BTT group.Conclusion: BTM significantly impaired liver and kidney function, while BTT showed mild increases in ALT, TBIL, DBIL, creatinine, and ferritin. In BTM, ferritin correlated with ALP, indicating potential iron toxicity, whereas in BTT, the negative correlation with creatinine may suggest a protective mechanism. Further research is needed to clarify ferritin thresholds for toxicity versus protection.